From Farm to Fork : Perspectives on Growing Sustainable Food Systems in the Twenty-First - Morath, Sarah (Book collections on Project MUSE., 2016)
"Interest in the food we eat and how it is produced, distributed, and consumed has grown tremendously in the last few years. Consumers are exchanging highly processed, genetically engineered, and pesticide-contaminated food for fresh produce grown using organic methods. For example, in both urban and rural areas, the number of farmers markets has grown from 1,755 in 1994 to 8,200 in 2014. This change is just one indication consumers are interested in knowing who produced their food and how it was produced. This book addresses the importance of creating food systems that are sustainable by bringing together a number of experts in the fields of law, economics, nutrition, and social sciences, as well as farmers and advocates. These experts share their perspectives on pressing issues related to sustainable food systems and offer solutions for achieving healthy, sustainable, and equitable food systems in the future."--Page [4] cover.